Pengaruh Pengajaran Pendidikan Agama Kristen melalui Ibadah Online terhadap Pembentukan Karakter Remaja Pemuda - Mikha Agus Widiyanto (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
Teaching given in a worship as a part of Christian Religious Education duty which plays an important role in adolescent and youth character building. In COVID-19 pandemic, worship is being an affected aspect, so that it is held online. Christian Religious Education teaching delivered through online will affect adolescent and youth worship intensity. When online service considered as less attractive, it will affect their solemnity in involvement of the worship and the character formation. This research aimed to study the influence Christian Religious Education teaching through online service to adolescent and youth character building. Method used was survey. The result showed that is a significant influence of the Christian Religious Education teaching to the adolescent and youth character building. The teaching given attractively and suitable to the adolescent and youth needs in online service will make Christian Religious Education teaching effective, so that they can implement it in daily life indicated by character changes to be like Christ.